The impact of teaching communication strategies on EFL learners’ Willingness to Communicate - Mesgarshahr, Abulfazl; Abdollahzadeh, Esmaeel (Studies in Second Language Learning and Teaching, 2014)
One of the pedagogical implications of the research on the Willingness to Communicate (WTC) might be to propose practical ways of making language learners more willing to communicate in the classroom. This study investigated the impact of teaching communication strategies (CSs) on Iranian EFL learners’ WTC. To this end, 8 intact classes were included as the experimental and control groups. The control group underwent regular language instruction, while the experimental group received the treatment (i.e., communication strategy training). The self-report measurement of WTC (MacIntyre, Baker, Clément, & Conrad, 2001) was done before (pre-test) and after the treatment (post-test). The results of the independent-samples t test showed that the degree of WTC of the treatment group was significantly higher compared with that of the control group. It was concluded that teaching CSs helps learners become more willing to communicate in the classroom.